Self-initiated Academics Work Adjustment: A Systematic Literature Review - Farah Kalmey (European Scientific Journal, ESJ, 2023)
Expatriation abroad for work and leisure is becoming the norm these days. This necessitates individuals to adjust to life in their new destination and work environment. The purpose of this paper is to present a systematic review of the literature about how the phenomena of SIE academics adjust to their work environment. Method: A systematic literature search was conducted by searching for articles that were published in the field of SIE academics and no restrictions were placed on date of publication because of the nascent nature of the subject of study.  The following electronic databases were searched where language was restricted to only English: Business Source Complete, Academic Search Ultimate, Scopus, Web of Science and PsycINFO. Result: The result shows that SIEs face challenges that could affect their adjustment to life in a new country, culture and work. Among these factors are family, local language proficiency, interaction with local hosts and expatriates, prior international work experience and trainings provide at the work place. Another important issue that came up is differentiated treatment of expatriates based on their looks and passport they hold by the HCNs (host country nationals).